Philippines : Mid-2006 Post-Program Monitoring Discussions Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Philippines. (IMF Staff Country Reports; Country Report ;, 2006)
Macroeconomic performance has been relatively strong, and the large fiscal adjustment and the VAT reform represent significant progress in strengthening the fiscal position. Progress with reforms sets the stage for resolving longstanding economic problems. Tax collections have grown strongly. Over the medium term, sustainable fiscal consolidation will require a further revenue effort. Privatization of power sector assets should move ahead. Risks to inflation seem evenly balanced. Although important challenges remain, steps are being taken to strengthen the banking sector. Capital market development is a priority.